PREFACE. Mémoires et patrimoines vivants de la traite négrière et l’esclavage - Françoise Vergès (In Situ)
In France, the memories of slave trade and slavery have been reactivated since 1998 when the country celebrated the 150th anniversary of the abolition of slavery. A law was voted in May 2001 which recognized slave trade and slavery as « crime against humanity » and set up a Committee whose task was to elaborate propositions in the fields of school, research and culture to further the knowledge of this history. A cultural and social movement has emerged in the ten years since the adoption of the law. In this contribution, Françoise Vergès argued that this movement has opened up new questions and led to a new methodology of reading the archives and looking at findings in archeology and at the ways in which museums on slavery are thought. Special attention must be paid to intangible culture which constitutes an important source created by the enslaved.